Shi-Zhen-An-Shen Decoction, a Herbal Medicine That Reverses Cuprizone-Induced Demyelination and Behavioral Deficits in Mice Independent of the Neuregulin-1 Pathway - Chao Ma; Yan Wu; Xinyao Liu; Yi He; Yuan Jia; Pei Chen; Dongqing Yin; Yanzhe Ning; Guoqiang Xing; Zuoli Sun; Hongxiao Jia (Neural Plasticity)
Shi-Zhen-An-Shen decoction (SZASD), a Chinese herbal medicine that is a liquor extracted from plants by boiling, has been reported to be effective in treating schizophrenia. However, the mechanism is unclear. Abnormal demyelination has been implicated in schizophrenia. The aim of this study was to investigate the effect of SZASD on myelin in demyelinated mice exhibiting schizophrenia-like behaviors. Sixty male C57BL/6 mice were randomly divided into six groups (n=10 per group): (1) control group, (2) cuprizone (CPZ, a copper chelator that induced demyelination, 0.2% w/w)+saline, (3) CPZ+low-dose SZASD (8.65 g·kg-1·d-1), (4) CPZ+medium-dose SZASD (17.29 g·kg-1·d-1), (5) CPZ+high-dose SZASD (25.94 g·kg-1·d-1), and (6) CPZ+quetiapine (QTP, an atypical antipsychotic that served as a positive treatment control, 10 mg·kg-1·d-1). Mice in groups 2-6 were treated with CPZ added to rodent chow for six weeks to induce demyelination. During the last two weeks, these mice were given an oral gavage of sterile saline, SZASD, or quetiapine. Behavioral tests and brain analyses were conducted after the last treatment. The brain expression of myelin basic protein (MBP) and neuregulin-1 (NRG-1) was assessed using immunohistochemistry and Western blots. CPZ induced significant schizophrenia-like behaviors in the mice, including reduced nest-building activity and sensory gating deficits. Hyperlocomotor activity was accompanied by significant reductions in MBP expression in the corpus callosum, hippocampus, and cerebral cortex. However, both QTP and SZASD significantly reversed the schizophrenia-like behaviors and demyelination in CPZ-fed mice. The QTP and medium-dose SZASD resulted in better therapeutic effects compared to the low and high SZASD doses. Reduced NRG-1 expression was observed in CPZ-fed mice compared with controls, but neither QTP nor SZASD showed significant influence on NRG-1 expression in the hippocampus. Together, SZASD showed a therapeutic effect on demyelinated mice, and the improvement of demyelination might not be through the NRG-1 pathway.